TEKANAN STRES ANAK DALAM KELUARGA PASANGAN PERNIKAHAN DINI (Studi Kasus Di Desa Godean Kecamatan Loceret Kabupaten Nganjuk) - Muhammad Muhyiddin Azzuhdi; Habibi Al Amin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
One of the social problems in Indonesia is the high rate of child marriage. In general, Indonesia is ranked 10th in the world, in the category of child marriage. Early marriage is defined in Law no. 16 of 2019 amendments to Law no. 1 of 1974 concerning Marriage, the minimum limit for marriages held by minors is 19 years for women and 21 years for men, This study aims to describe and analyze the characteristics of stress in children, the factors that influence children's stress and the parenting patterns of early married couples which cause stress in children. One of the characteristics is irritability, aloofness, changes in attitude, changes in behavior and changes in appetite. And the factors that cause stress in children are the age of the couple, lack of mental and emotional readiness, parental conflict and quarrels and financial limitations.This research uses qualitative field research methods, with an empirical normative approach, the author uses 3 techniques in this research, namely observation, interviews and documentation. The author also uses data analysis techniques in the form of objective interpretations.This research resulted in the finding that the occurrence of early marriage in Godean Village, Loceret District, Nganjuk Regency was caused by several factors including educational, economic and cultural factors. And then this marriage has an impact on children's stress due to the immature parenting style of early married couples in dealing with household problems.It is hoped that related parties such as the KUA, local religious leaders and village officials involved will provide education to the community and especially to teenagers, about the impact of early marriage in order to prevent unwanted marriages from occurring in Godean Village, Loceret District, Nganjuk Regency. And to parents to pay attention and provide adequate education, especially general science and religion.